👤

1. x + 11 > 17

2 . 5(x+4) = 4x - 3

3. 2x ≥ 10

4. x - 4 < 10

5. x + 4 > 5

6. 6x - 5 = 19

7. x - 5 = 12

8. 3x = 15

9. 15 - 6x > 51

10. 5x - 3 = x + 25

11. x + 3 = 9

12. x = 7 - 6x

13. x/8 ≤ 10

14. x/5 = 10

15. x = 5 +6


Sagot :

Answer:

1.) x > 6

2.) x = -23

3.) x ≥ 5

4.) x < 14

5.) x > 1

6.) x = 4

7.) x = 17

8.) x = 5

9.) x < -6

10.) x = 7

11.) x = 6

12.) x = 1

13.) x ≤ 80

14.) x = 50

15.) x = 11

Done

Step-by-step explanation:

1.) x + 11 > 17

( x + 11) + ( -11) > 17 + ( -11)

x + 11 - 11 > 17 - 11

x > 6

Answer: x > 6

2.) 5 ( x + 4 ) = 4x - 3

5x + 5 × 4 = 4x - 3

5x + 20 = 4x - 3

5x - 4x = -20 + 3

x = -23

Answer: x = -23

3.) 2x ≥ 10

2x 10

2 2

x ≥ 2 x 5

2

x ≥ 5

Answer: x ≥ 5

4.) x - 4 < 10

( x - 4 ) + 4 < 10 + 4

x < 14

Answer: x < 14

5.) x + 4 > 5

x + 4 - 4 > 5 - 4

x > 1

Answer: x > 1

6.) 6x - 5 = 19

6x - 5 + 5 = 19 + 5

6x = 24

6x = 24

6 6

x = 4

Answer: x = 4

7.) x - 5 = 12

x - 5 + 5 = 12 + 5

x = 17

Answer: x = 17

8.) 3x = 15

3x = 15

3 3

x = 5

Answer: x = 5

9.) 15 - 6x > 51

- 6x + 15 > 51

- 6x + 15 - 15 > 51 - 15

-6x > 36

-6x > 36

-6 -6

x < -6

Answer: x < -6

10.) 5x - 3 = x + 25

5x - 3 - x = x + 25 - x

4x - 3 = 25

4x - 3 + 3 = 25 + 3

4x = 28

4x = 28

4 4

x = 7

Answer: x = 7

11.) x + 3 = 9

x + 3 - 3 = 9 - 3

x = 6

Answer: x = 6

12.) x = 7 - 6x

x = 7 + -6x

x = -6x + 7

x + 6x = -6x + 7 + 6x

7x = 7

7x = 7

7 7

x = 1

Answer: x = 1

13.) x ≤ 10

8

1 ≤ 10

8

8 x ( 1 x) ≤ ( 8 ) × ( 10 )

8

x ≤ 80

Answer: x ≤ 80

14.) x = 10

5

( x ) x ( 5 ) = ( 10 ) x ( 5 )

5

x = 50

Answer: x = 50

15.) x = 5 + 6

x = 5 + 6

x = 11

Answer: x = 11

#HopeItWillHelpful